Kantian Ethics Towards A Justifiable Business And Trade Practices: Envisaging A Humanitarian Society - Chris O. Abakare (Universitas Negeri Makassar, 2021)
The Kantian code of ethics is guided by pure practical reason and since reason is consistent and permits no exceptions to favor the lawmaker or its adherent, the moral law is also consistent and inflexible. This nature of the law is very significant for trade as trade norms cannot be flexed to favor a particular nation or company. This paper believes that Kantian cosmopolitanism should be the credo of business and trade. The reason for this assertion is because the ultimate goal of humanity is a prosperous living of all people in a spirit of unity. Humanity is at its best when rising above the barriers of race, caste and creed. And Kant's ethics has always recommended a path for humanity that leads to this cohesion. Ethical commonwealth, cosmopolitanism, League of Nations and Kingdom of ends have in themselves this one-point agenda to envisage a humanitarian society that takes pride in peaceable solidarity of human existence.